2021
DOI: 10.51220/jmr.v16i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Macrozoobenthos of Basti Damar Stream in Rudraprayag District, Garhwal, Uttarakhand: Diversity and Habitat Analysis

Abstract: Basti Damar gad is a spring fed tributary of river Mandakini which is quite conducive for biodiversity. As the stream was unexplored, it was taken as an opportunity to investigate the stream for its habitat quality and diversity of benthic organisms. Stream was studied at two different spots one in more or less rhithron zone and the other one in near potamon zone during the year 2019-20. Comparatively, the Spot No 2 had more density (836 individules.m-2 ) and diversity (28genus) of macrozoobenthos than spot No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Authors observed rich epilithic periphyton and detritus standing stock along with macrozoobenthos. Periphyton diversity and distribution concerning stream physicochemical parameters have a huge impact on the occurrence of several mites Pesic et al, 2019a,b;2020a,b;, macrozoobenthos (Kumar and Dobriyal, 1999;Rautela et al, 2006;Bahuguna and Dobriyal, 2018;Mamgain et al, 2021) and drifting behaviour of invertebrates Bahuguna and Dobriyal, 2020; and on fish diversity (Bahuguna et al, 2010;Bahuguna and Joshi, 2012;Bahuguna 2020Bahuguna , 2021Rayal et al, 2021a,b). Dobriyal (2017, 2018) have worked on the riparian vegetation of Western Nayar and reported that they form detritus and hence positively affect the production of macrozoobenthos and fishes.…”
Section: Resultsmentioning
confidence: 99%
“…Authors observed rich epilithic periphyton and detritus standing stock along with macrozoobenthos. Periphyton diversity and distribution concerning stream physicochemical parameters have a huge impact on the occurrence of several mites Pesic et al, 2019a,b;2020a,b;, macrozoobenthos (Kumar and Dobriyal, 1999;Rautela et al, 2006;Bahuguna and Dobriyal, 2018;Mamgain et al, 2021) and drifting behaviour of invertebrates Bahuguna and Dobriyal, 2020; and on fish diversity (Bahuguna et al, 2010;Bahuguna and Joshi, 2012;Bahuguna 2020Bahuguna , 2021Rayal et al, 2021a,b). Dobriyal (2017, 2018) have worked on the riparian vegetation of Western Nayar and reported that they form detritus and hence positively affect the production of macrozoobenthos and fishes.…”
Section: Resultsmentioning
confidence: 99%
“…Khanda Gad stream has been reported to have 14 different species of water mites (Acari: Hydrachnidia) (Kumar and Dobriyal, 1992;Pesic et al, 2004;2007a-b;Kumar et al, 2007;Bahuguna and Negi, 2021). Periphyton diversity and distribution in relation to stream physicochemical parameters have a significant impact on the occurrence of several aquatic mites (Pesic et al, 2020ab;2022a,b;Baluni et al, 2017Baluni et al, ,2018Baluni et al, ,2020Bahuguna et al, -b, 2020aBaluni 2020;Negi et al, 2021a,b), drifting behaviour of micro and macrozoobenthos (Bahuguna et al, 2019b(Bahuguna et al, , 2020bDobriyal, 2020,2022) and on the diversity of fishes (Rayal et al, 2021 a,b;Bahuguna 2020Bahuguna ,2021Bahuguna and Joshi, 2012;Bahuguna et al, 2010) as well as macrozoobenthos (Rautela, et al, 2006;Bahuguna and Dobriyal, 2018;Kumar and Dobriyal, 1999;Mamgain et al, 2021) Declaration: We also declare that all ethical guidelines have been followed during this work and there is no conflict of interest among authors.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous authors noted the presence of macro and microzoobenthos along with rich epilithic periphyton and debris standing stock (Bahuguna et al, 2021). The diversity and distribution of periphyton in relation to the physicalchemical characteristics of streams greatly influence the presence of various aquatic mites (Kumar and Dobriyal, 1992;Balodi et al, 2004;Pesic et al, 2020a-b;2022a,b;Baluni et al, 2017Baluni et al, , 2018Baluni et al, , 2020Bahuguna et al, 2019aBahuguna et al, , 2020aBaluni 2020;Negi et al, 2021a,b;Rana et al, 2022), macrozoobenthos (Rautela et al, 2006;Kumar and Dobriyal, 1999;Bahuguna and Dobriyal, 2018;Mamgain et al, 2021), drifting behavior of macrozoobenthos (Bahuguna et al, 2019b(Bahuguna et al, , 2020bBahuguna and Dobriyal, 2020) and on fish diversity (Bahuguna et al, 2010;Bahuguna and Joshi, 2012;Rayal et al, 2021 a, b).…”
Section: Discussionmentioning
confidence: 99%